Functional studies of p.R132C, p.R149C, p.M283V, p.E431K, and a novel c.652-2A>G mutations of the CYP21A2 gene - Taboas, Melisa (2014)
Fil: Taboas, Melisa. ANLIS Dr.C.G.Malbrán. Centro Nacional de Genética Médica; Argentina.